Register on the Documenter “Becoming”: Sociolinguistics Study - Haezar, Rudi Eben; Simatupang, Ervina CM (Universitas Veteran Bangun Nusantara, 2024)
The purpose of this study is to categorize the various registers and examine the ethnographic communication variables in the documentary movie titled Becoming. A descriptive qualitative analytic strategy was employed in this study. The information is derived from interviews that are featured in the documentary Becoming. The present study employs three theoretical frameworks related to Sociolinguistics: the register type’s theory proposed by Joos (1967), the ethnography of communication components theory from Hymes (1974), and the context theory from Cutting (2002). For around 22 data conducted from the discourse in the documentary Becoming are analyzed in this study. The result shows that one frozen register, seven formal registers, three consultative registers, seven informal registers, and four intimate registers, according to the research. There are 109 communicative ethnography elements identified from 22 data. The elements that are most frequently present in the data are instrumentalities, setting and scene, and setting. Participants, endpoints, acts of sequences, keys, and genres are the other aspects.